Social and financial effciency of microfinance institutions : Developing markets, macro environment and financial inclusion - Soldátková, Natálie (2020)
The microfinance industry was established with the main purpose to provide financial services to people who generally have no access to traditional banking because of their low, irregular or unpredictable income. The microfinance industry is expanding rapidly with an annual growth of over 9% in the global portfolio of loans and the number of active borrowers, serving around 123 million customers worldwide (Microfinance Baromoter, 2017). Financial environments where microfinance institutions operate differ from country to country, from unregulated to highly regulated, from fully digitized to paper-based. One naturally raised question is what is the social efficiency, financial efficiency and relation between both for microfinance institutions when compared across different economies, and to what extent do market conditions and internal strategic decisions impact on this efficiency. Using the database of financial, operational and social performance indicators of service providers in 38 countries of the Sub-Saharan African region, the first part of this work describes the results of an empirical study of social and financial efficiency. This is based on the Data Envelopment Analysis modelling approach for the period of 2004-2017. Hyperbolic non-oriented DEA models, super-efficiency DEA models, Ray-Desli Malmquist Index and Circular Malmquist Index were employed. Further relation between internal institutional and external environmental factors and efficiency level has been assessed using non-parametric Kruskal–Wallis tests. The internal factors included in the research are the presence of a deposit scheme, gender focus, customer target group and the prevailing term of the loan.